Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-61 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
The 10-year-old SCI patient Nefeli during training with the hula hoop to improve trunk mobility/stability and balance.